Register as the Situational Variety of Language (Proceedings of Southern Federal University. Philology, 2016)
Natalya B. Boyeva-Omelechko, Alina K. Kisil (Southern Federal University, Rostov-on-Don, Russian Federation)The problem discussed in the article is topical due to the interest of scientists to different types of language variations and especially registers or situational dialects treated by M.A.K. Halliday as use-related varieties of language or varieties used in a particular social setting. As discourse categorization is a very complex problem scholarly consensus has not been reached for the definitions of the term «register». The universal criteria for defining and discriminating registers have not been worked out either. The authors of the article give the review of scientific works devoted to the problem in question especially works by M.A.K. Halliday, R. Quirk, M. Joos, D. Hymes P. Trudgill, E.I. Belyaeva and others and analyze different definitions of the term «register», spectrums of registers and criteria for their discriminating. It enables the authors to come to the conclusion that only registers with the same field (religious, political, business etc.) and mode (oral/written, dialogue/monologue) can be compared. The difference lies in the sphere of tenor which depends on the degree of formality, distance of power and socio-psychological distance between speakers. The authors believe that it is also necessary to take into account the cooperative/ uncooperative character of conversation and para-verbal and non-verbal components of the speech situation. With this in mind they offer their definition of the register and describe main characteristics of registers in the sphere of oral communication.Key words: situational variation, speech situation, register, situational dialect, dialogue, tenor, style, scale of formality, distance of power, scale of formality, socio-psychological distance, cooperative/uncooperative character, verbal, para-verbal and non-verbal means.DOI: 10.18522/1995-0640-2016-4-93-101